"Physics envy" in organisation studies: the case of James G. March. Issue 2 (11th October 2021) - Joullié, Jean-Etienne; Spillane, Robert
Abstract : Purpose: This article aims to propose a critical review of James G. March's research in and particular its consistency with its epistemological and psychological underpinnings. Design/methodology/approach: The paper proposes a textual and conceptual analysis of James G. March's study. Findings: The article argues first that March's study exemplifies the "physics envy" typical of management and organisation studies scholars since the early 1960s. Second, evidence is presented that March's conclusions, irrespective of their legacy on management and organisation studies, were not developed along and were not consistent with the foundations that March espoused and advocated during most of his career. As a result, the implications of his conclusions are uncertain. To his credit, however, there are reasons to believe that, towards the end of his career, March came to recognise the limitations of his scholarship. Further, he indicated an alternative avenue for organisation studies which eschews the shortcomings of positivist and post-modern research. Research limitations/implications: Although centred on March's work, the argument presented is relevant to psychology, organisations, choice, the nature of knowledge, the limitations of positivism and post-modernism. Originality/value: The paper balances the perspective offered by recent celebratory reviews of March's study.